An ANALYSIS OF TEACHERS’ STRATEGIES IN TEACHING ENGLISH SPEAKING SKILL - Ridho Kurniawan; Yahfenel Evi Fussalam; Tri Saswandi (Journal Of Language Education and Development (JLed), 2021)
This study seeks to determine the types and frequency of tactics employed by teachers in teaching English speaking. This study focused on the English instructors in Jambi. The data was qualitatively examined. The findings revealed that the teachers employed four distinct tactics. These were enhancing student discourse, developing role play, developing narratives, and training interviews. In teaching English as a second language, role-playing was the most prevalent approach employed by teachers. Teachers determined that by implementing the developing role play technique, pupils became more active and confident when playing a role based on the materials provided by the teachers. In addition to making students more passionate about learning English, role-playing encouraged them to engage in more conversation with their classmates and peers.Keywords :Analysis, Strategy, Public Speaking